PENGARUH TATA LETAK PERABOT TERHADAP RUANG GERAK PADA UNIT HUNIAN APARTEMEN DAGO BUTIK - Phanduwinata, Vici (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Parahyangan, 2009)
Abstract The growth of multi-family housing in the form of apartment in big cities in Indonesia, especially in Bandung, has been a phenomenon nowadays. Dago, which is located in northern Bandung, has become an area that grows rapidly in apartment building. Dago Butik Apartments in this area is one of the examples of the phenomenon. This apartment has various types of units offered to the users, most of them are mid-high class people. Dago Butik Apartments has 6 types of units in 16 different levels. Each type has different dimensions. This study will analyze about the effectivity and efficiency of the units in this apartment. Effectivity and efficiency are one of the most important things in designing a building, including apartment. These factors can be seen in the effectiveness and the efficiency of the units design. The space formed in the apartment units is linked to the activity pattern and the inhabitants need. In this paper, the effectivity and efficiency will be linked to the tenants activities. Through the analysis, the pluses and minuses of Dago Butik Apartment units will come out. In general, it can be told how a unit can be effective and efficient. Key Words: apartment, housing unit, effectivity, and efficiency Abstrak Pesatnya pembangunan